The correlation between plasma lactoferrin and inflammatory biomarkers in type 2 diabetes with dry eye disease patients - Amani Y. Alhalwani; Amani Y. Alhalwani; Shatha Jambi; Shatha Jambi; Husain Alalgum; Hawazen Zarif; Hawazen Zarif; Hawazen Zarif; Sarah Alshareef; Sarah Alshareef; Sarah Alshareef; Abrar Babgi; et al. (Frontiers in Medicine, 2025)
BackgroundLactoferrin (LF) is a primarily protein derived from the degranulation of neutrophils in plasma, and has been identified as a potential biomarker for dry eye disease (DED) and type 2 diabetes patients (T2D). This study aims to investigate the correlation between plasma lactoferrin and other inflammatory biomarkers, such as lactoferrin to neutrophil ratio (LFNR) and glycosylated hemoglobin A1c (HbA1C), in type 2 diabetic patients with dry eye disease (T2D-DED).MethodThis study was conducted at the Diabetes Center outpatient clinics at King Abdulaziz Medical City, Jeddah, Saudi Arabia. The study included two groups: 26 healthy individuals and 41 T2D-DED patients. The plasma samples were collected and analyzed in the hospital for laboratory routine tests for neutrophil, lymphocyte, C-reactive protein (CRP), glycosylated hemoglobin A1c (HbA1C), and albumin (ALB), and data were collected retrospectively from hospital medical records. The same plasma samples were tested for LF using an in-house enzyme-linked immunosorbent assay (ELISA). The plasma lactoferrin to neutrophil ratio (LFNR) and neutrophil to lymphocyte ratio (NLR) were calculated. All statistical analyses were performed using PRISM software, with a p-value < 0.05 were considered significant.ResultsLF concentrations were found to be 1.10 ± 1.0 μgmL−1 in T2D-DED patients and 0.5 ± 0.4 μgmL−1 in healthy individuals. Inflammatory biomarkers, LF, CRP, HbA1C, and LFNR, showed elevated levels in patients with T2D-DED, with statistically significant differences groups compared to healthy individuals. Additionally, there was a significant positive correlation in T2D-DED patients between LF with LFNR in T2D-DED patients (p = 0.0001) and HbA1C with LF (p = 0.035).ConclusionThe study indicated that LF levels and other inflammatory biomarkers are elevated in patients with T2D-DED. There are significant positive correlations between LF and HbA1C, as well as LF and LFNR in T2D-DED patients, which differ from the correlations found in healthy individuals. This suggests that the diagnostic and prognostic relevance of these biomarkers depends on whether the disease is present.